A Literature Review of Financing the Tertiary Education In Indonesia - Virza Alamsyah (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2020)
This article was written to review three financial journals in higher education. The evaluation of this article aims to identify the strengths and weaknesses contained in these three articles. Higher Education Financing is one of the issues related to many countries, and this is related to inclusive education, namely education for all people. As a large country with a vast population, Indonesia is faced with the obligation to provide the right to education for all Indonesian citizens. The three journals' results must be that the government actively runs work schemes for students and support private universities so that the number of education participation can increase significantly.